(untitled) (Balneo and PRM Research Journal, 2024)
: This systematic review examines groundbreaking advancements in hand rehabilitation, driven by significant progress in medical technology. Adhering to PRISMA guidelines, the review surveyed articles from various databases, emphasizing the utilization of advanced technologies for hand rehabilitation across diverse conditions such as fractures, burns, amputations, and postoperative care. Out of the 1562 studies analyzed, ten articles that met the inclusion criteria were identified. Key technologies like IMES (Implantable Myoelectric Sensor) technology are scrutinized for their potential to transform prosthetic control, providing intuitive functionality and substantial physiological hand function for individuals with limb loss. Similarly, advancements in orthotic devices like the VacoHand Orthosis are showcased for their improvements in stabilizing and aiding the healing process in wrist immobilization and rehabilitation. The integration of virtual reality (VR) emerges as a pivotal convergence point, offering supplementary therapy to enhance direction-specific improvements in wrist and forearm mobility, hand function, and work-related tasks. Additional advantages include program customization, heightened engagement through interactive approaches, and improved functional outcomes such as hand strength and range of motion. While showcasing transformative potential, the review acknowledges the need for further research through larger sample sizes, standardized methodologies and more in-depth investigations to optimize these technologies. Overall, this review underlines the remarkable advancements achieved in hand rehabilitation through technological innovations, offering hope and improved outcomes for individuals grappling with various hand-related challenges.